موقف الإعلام العربي من الثورة الجزائرية (1954-1956م) "تونس ومصر نموذجا" - بن مهدي, مرزوق; الدام, محمد (جامعة الوادي - University of Eloued, 2022)
لاقت الثورة الجزائرية منذ تفجيرها في أول نوفمبر 1954م اهتمامًا واضحًا في الرأي العام العربي والعالمي، فقد تعدى الدعم النطاق العربي، إلا أنه كان محدود نظرًا لخضوع تلك الدول للسيطرة الاستعمارية، ليبرز دور تونس ومصر الفعال الذي جُسد في دعم الحركة الوطنية الجزائرية، حيث أبدوا استعدادهم التام لدعم وتأييد الثورة الجزائرية في حالة انطلاقها، سواء كان هذا الدعم عسكريًا أو إعلاميًا أو سياسيًا، وهكذا كانت تونس ومصر السباقتين في دعم نضال الحركة الوطنية الجزائرية والثورة الجزائرية. وقد حظيت الجزائر بدعم مادي ومعنوي من بعض الدول العربية المغاربية والمشرقية، اختلفت مظاهره من دولة إلى أخرى قبل وأثناء الثورة التحريرية، ويمكن الإشارة في هذا السياق إلى دور الدعم الإعلامي الذي لعبته تونس ومصر على وجه الخصوص كقاعدة خلفية للثورة الجزائرية واحتضانها لقادة الثورة ومؤسساتها وشخصياتها البارزة سواء كانت سياسية أو عسكرية منها. Abstract: Since its bombing on the first of November 1954, the Algerian revolution has received clear attention in Arab and international public opinion, as support has gone beyond the Arab domain, but it was limited due to the subjection of those countries to colonial control, to highlight the effective role of Tunisia and Egypt, which was embodied in support of the Algerian national movement, where they showed their willingness Full support and support for the Algerian revolution in the event of its launch, whether this support was military, media or political, and thus Tunisia and Egypt were the first to support the struggle of the Algerian national movement and the Algerian revolution. Algeria has enjoyed material and moral support from some Arab Maghreb and Levantine countries, its manifestations differed from one country to another before and during the liberation revolution. Be it political or military ones.
The position of the Arab media on the Algerian (1954-1956) Tunisia and Egypt as a model
مقال
Keywords: صدى الثورة الجزائرية، موقف الإعلام العربي، تونس، مصر.; echo of the Algerian revolution, the position of the Arab media, Tunisia, Egypt.